Pre-graduation practice programme - Prokhorenko, O. V.; Uhrimova, I. V.; Solopun, N. M. (National Technical University "Kharkiv Polytechnic Institute", 2025)
The guidelines are developed for students studying in programs of specialty 073 "Management", first (Bachelor’s) level of higher education. The guidelines describe the content of the Pre-graduation Practice, the topicі of individual tasks, the requirements for the practice report, and also define the main provisions regarding the Practice organizing.
Програма проходження переддипломної практики
Keywords: programme; objectives; tasks; permission request; letter of consent; topics; assessment; grading